2022
DOI: 10.1007/s11160-022-09736-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of sensory deterrents for bycatch mitigation of marine megafauna

Abstract: Marine megafauna are critical for marine ecosystem health and their removal can cause food webs to collapse. Methods to reduce marine megafauna mortality can result in conflict between scientists, conservationists, fishers and fisheries management due to real or perceived effects on target catch, income and food security. Sensory deterrents have been used in attempts to mitigate bycatch and retain target catch quantity and quality. Here, we completed a systematic review of 116 papers, plus 25 literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…Measures to mitigate the impact of PLL by-catch include adaptations of the gear, fishing area, bait, soak time, and setting and hauling times of the longline (Bigelow and Maunder, 2007;Coelho et al, Gilman et al, 2016). The adaptations of the gear include the distance between floats, which affects the hook fishing depth (Afonso et al, 2012), the material of the leaders and/or branch lines (e.g., wire or nylon) (Afonso et al, 2012), the use of repellent (e.g., chemical or magnetic) (Lucas and Berggren, 2022), and hook size and shape (Piovano and Gilman, 2017). The gear modification that is the most commonly tested is hook shape (e.g., Kim et al, 2006;Piovano et al, 2009;Ward et al, 2009;Sales et al, 2010;Pacheco et al, 2011;Afonso et al, 2012;Coelho et al, 2012;Godin et al, 2012;Gilman et al, 2016;Piovano and Gilman, 2017;Guo et al, 2022) probably for being a relatively low-cost by-catch mitigation measure (Gilman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Measures to mitigate the impact of PLL by-catch include adaptations of the gear, fishing area, bait, soak time, and setting and hauling times of the longline (Bigelow and Maunder, 2007;Coelho et al, Gilman et al, 2016). The adaptations of the gear include the distance between floats, which affects the hook fishing depth (Afonso et al, 2012), the material of the leaders and/or branch lines (e.g., wire or nylon) (Afonso et al, 2012), the use of repellent (e.g., chemical or magnetic) (Lucas and Berggren, 2022), and hook size and shape (Piovano and Gilman, 2017). The gear modification that is the most commonly tested is hook shape (e.g., Kim et al, 2006;Piovano et al, 2009;Ward et al, 2009;Sales et al, 2010;Pacheco et al, 2011;Afonso et al, 2012;Coelho et al, 2012;Godin et al, 2012;Gilman et al, 2016;Piovano and Gilman, 2017;Guo et al, 2022) probably for being a relatively low-cost by-catch mitigation measure (Gilman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Traps and pots are potential alternative fishing gears for gillnets and trammel nets because of their relatively low CPUE for marine megafauna. Light‐emitting diode lights on gillnets (Lucas & Berggren, 2022), acoustic deterrent devices or ‘Pingers’ (Gazo, Gonzalvo & Aguilar, 2008; Dawson et al, 2013), by‐catch reduction devices, and turtle excluder devices (Willems et al, 2016) can reduce megafauna catch and should be considered as part of future mitigation methods and regulations. Furthermore, if training is provided for the fishers and marine/coastal officers on best practice to release any live caught cetacean, dugong, sea turtle, or elasmobranch, this may substantially decrease by‐catch mortality and increase post‐capture survival (Zollett & Swimmer, 2019; Hamer & Minton, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…O'Neill et al (2019) also suggested that passive acoustic approaches with sound reflectors can be designed with gears to make them more detectable for echo-locating species (He, 2010). Mainly, sound and light added to fishing gears can help attract the targeted species and help deter vulnerable or harmful animals such as mammals or fish predators (Putland and Mensinger, 2019;Lucas and Berggren, 2022). Although fishing techniques with sound have been in practice since a while (He, 2010), exploration for species selective sound devices are still at its early stages.…”
Section: Responses To Acoustic Stimulimentioning
confidence: 99%